Politik Tubuh Perempuan: Studi Tes Genitalia pada Perekrutan Anggota Polisi Baru di Indonesia - Pratama, Abdul Azis (ijd-demos, 2019)
The focus of this research is to see how Body, Sex, and Norm play a role in Women’s Subjugation in Indonesia. As a conservative and moslem majority country, Indonesia often finds herself strangled in the Sexist Situation. Whereas Men had been granted a greater role in public affairs and more excepted to be a leader, than its companion gender. Besides not having the same opportunity as men in public affairs, Women in Indonesia also faced a subjugation of their body and their ‘morale’. It is said, that one of the Indonesian norms is to forbids Women to have pre-marital sex, and to do so they have to cover their bodies, and not to be too friendly to Male Strangers. However, this standard doesn't apply to Men, which leads to a situation where Women’s become a more inferior gender in terms of personal expression. But the problem didn’t stop there, Women who caught already have a pre-marital sex (determined by the intactness of Hymen) will faced another discrimination, such as social judgment, excommunication and exclusion in several employment, for Instance in Kepolisian Republik Indonesia (Indonesian Police Force). Fokus penelitian ini adalah untuk melihat bagaimana politik tubuh, jenis kelamin dan norma yang berperan dalam seleksi masuk kepolisian indonesia. Sebagai negara mayoritas yang konservatif dan mayoritas beragama Islam, Indonesia sering menemukan posisi-posisi yang menyudutkan perempuan dalam Situasi yang tidak setara. Sedangkan Pria telah diberikan peran yang lebih besar dalam urusan publik, dan lebih dikecualikan untuk menjadi pemimpin, daripada gender pendampingnya. Selain tidak memiliki kesempatan yang sama dengan laki-laki dalam urusan publik, Perempuan di Indonesia juga menghadapi penaklukan tubuh dan 'moral' mereka. Penelitian ini mengelaborasi mengenai posisi perempuan dalam seleksi menjadi anggota polri, dima tubuh mereka  menjadi sebuah objek yang harus dijaga dalam sebuah status keperawanan. Riset ini juga melihat bagaimana isu yang berkembang dalam tes kesehatan yang melihat lebih jauh tubuh perempuan sebagai objek yang harus di jaga. Dengan pendekatan fenomenologi, riset ini akan lebih mengelaborasi segala objektifikasi terhadap tubuh perempuan.